2014
DOI: 10.5588/ijtld.13.0602
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index predictive of sputum culture conversion among MDR-TB patients in Indonesia

Abstract: Severe underweight was associated with longer time to initial sputum culture conversion among MDR-TB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
8
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 0 publications
9
41
8
5
Order By: Relevance
“…The double effect of smoking behavior, Diabetes mellitus and the nutritional deficiencies as risk factors for TB and delayed conversion have been described (Bhargava et al, 2013;Putri et al, 2014;Agrawal, 2017;Nakamura et al, 2014;Shariff and Safian, 2015;Guanche et al, 2016;Long and Schwartzman, 2013;Cegielski et al, 2012;Magee et al, 2014;Tachouti et al, 2011). The low frequency of active smoker, the mandatory admission for infectious patients and the compliance with the non-smoking policy in healthcare facilities could be related to our results.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The double effect of smoking behavior, Diabetes mellitus and the nutritional deficiencies as risk factors for TB and delayed conversion have been described (Bhargava et al, 2013;Putri et al, 2014;Agrawal, 2017;Nakamura et al, 2014;Shariff and Safian, 2015;Guanche et al, 2016;Long and Schwartzman, 2013;Cegielski et al, 2012;Magee et al, 2014;Tachouti et al, 2011). The low frequency of active smoker, the mandatory admission for infectious patients and the compliance with the non-smoking policy in healthcare facilities could be related to our results.…”
Section: Discussionsupporting
confidence: 70%
“…The conversion time has been related with multiple factors including nutritional factors such as anemia, magnesium level, and body mass index (Bhargava et al, 2013;Putri et al, 2014;Agrawal, 2017), history of diabetes mellitus and poor metabolic control (Mi et al, 2013;Nakamura et al, 2014;Sharif, 2015), bacillary load in the diagnosis (D'Souza et al, 2018;Kanda et al, 2015;Gunda, 2017), diagnosis delay and radiological lesions suggestive of extensive damage or cavitation (Mi et al, 2013;Nakamura et al, 2014;Unsematham and Kateruttanakul, 2013;Visser et al, 2012) and drug resistance (Kim et al, 2016;Holtz et al, 2006;Kurbatova et al, 2012). A previously published paper identifies the bacillary load in the diagnosis as the main factor related with sputum conversion in patients attended to in a community hospital in Qatar, but the study is limited by the number of patients studied (64 patients) (Guanche et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…XDR-TB can be primarily transmitted from person to person or secondary to the development through high bacillary load, inadequate treatment (poor compliance, iatrogenic, drug stock outs, programatic weakness), low body mass index, or previous failures [34][35][36][37][38]. Prevention of the development of drug-resistant TB is essential given the recent worldwide increase in incidence.…”
Section: Prevention Of Xdr-tb During Mdr-tb Treatmentmentioning
confidence: 99%
“…It is supported by a study by Hicks et al (2014) which revealed one one the factors influence MDR TB incidences and even continued to death namely poor nutritional status on TB patients. Putri et al (2014) mentioned that poor nutritional status caused treatment of the patients became less effective and prevent the occurrence of sputum culture conversion in the initial phase of MDR TB treatment. It is elaborated by Park et al (2016) and Tang et al (2013) that poor nutritional status is often discovered on patients who endure resistance to TB medication because of the decreasing body immune that disturb immune system toward mycobacteruim tuberculosis.…”
Section: The Association Between Nutri-mentioning
confidence: 99%